Elderly’s Dependency Level Correlated with the Burden Perceived by Informal Caregivers - Maria Prieska Putri; Oda Debora; Eli Lea (Journal of Ners and Midwifery, 2023)
Elderly care at home is quite heavy care related to various physiological and psychological changes in the elderly. Informal caregivers who takecare for elderly may get increase burden experience, especially for elderly people with a high level of dependency. The aim of this research is to determine the correlation between the level of elderly dependency and the burden felt by informal caregivers. This research was a non-experimental quantitative research with a cross-sectional design. The research was carried out in March-August 2023 with the population of 137 informal caregivers in Sukoharjo Hamlet, Klojen District, Malang City, East Java. The sample was 102 respondents who was carried out randomly using simple random sampling technique. The independent variable in this research was the level of elderly dependency. There was a correlation between the level of elderly dependency and the burden felt by elderly caregivers with a significance value of <0.05. Based on the research results, it showed the correlation between the level of dependency of the elderly and the burden felt by the caregiver. The various physical burdens felt by caregivers while caring for the elderly, if it is not applied with a good management, it can affect to the daily activities. The caregiver’s busy schedule in caring for the elderly give impact to disruption their social life and the caregiver loses the time to enjoy their personal needs.